Traces of Linguistic Imperialism Enacted through Discursive Strategies in ELT Textbooks in Indonesia - Ahmad Budairi (English Language Teaching Educational Journal, 2018)
Although in many educational contexts textbooks serve as the backbone of teaching, providing practical guides for teachers as well as useful references for learning progress, they could also serve as a site of struggle for many competing discourses. ELT textbooks bear particular relevance here, as they place English at the center of prominence while serving as a medium for knowledge transmission. This paper reports on part of the findings of a case study examining the exercise of dominant discourses in two ELT textbooks for high school in Indonesia. The analysis revealed that there are imbalanced power relations—enacted through such discursive strategies as foregrounding,, backgrounding and framing in two areas: topics and visuals. These strategies were understood as part of the author’s attempt to preserve the hegemonic status of English and its associated dominant ideology in ways that reflect traces of linguistic imperialism. With regard to the pedagogical value of the textbooks, this paper offers some suggestions on how the textbooks could be more engaging and culturally sensitive towards learners’ socio cultural context. The discussion concludes with an appeal for more balanced representation between the discourse of the third world and that of Britain in ELT textbooks in Indonesia.